An economic assessment of alternative antimicrobial use scenarios on pig farms - Shrestha, Shailesh; da Costa, Maria R.; Correia-Gomes, Carla; Nevel, Amanda; McGowan, Andy; Tongue, Sue C. (Frontiers in Veterinary Science, 2024)
This paper explores the theoretical economic outcome of management changes that result in different levels of antimicrobial use (AMU) in two types of UK pig farm. A static farm economic pig production model (FEPM) was used on a representative ‘Top-third’ most profitable farm and a representative ‘Mid-range’ profitable farm. Three AMU theoretical management scenarios were investigated; a) management changes leading to a reduction of AMU by 35% (AMU35); b) more extensive management changes leading to a reduction of AMU by 95% (AMU95); and c) implementing depopulation of the herd (AMU Depop). A sensitivity analysis was conducted to determine the effect of increases or decreases in pig revenue and feed price on farm gross margin under these scenarios. Over a single year, the AMU35 scenario was estimated to have a small positive impact (+3%) on both farm types. The other two AMU reduction scenarios had higher AMU reduction on farms but required higher variable cost and hence they resulted in lower farm profitability. There was a substantial reduction (up to -50%) in farm gross margin under these two AMU reduction scenarios in the modelled short-term time-period. The impact of the alternative AMU scenarios was slightly higher on a farm representing the ‘Top-third’ farm type, reducing farm gross margin further by 7% compared to the ‘Mid-range’ farm. Nevertheless, both farm types stay profitable under all three AMU scenarios. The results showed that in the modelled short-term implementing management changes that result in a reduction of on-farm AMU by 35% had a good economic outcome. In practice, the other two scenarios would be considered as longer-term strategies. Although both require higher initial costs to implement, the improved biosecurity and hygiene will benefit from lower disease occurrence for a longer term. Farm gross margins were, however, found to be highly sensitive to changes on market prices especially increasing feed prices. An increase of more than 15% in feed price moved a profitable farm into a loss-making farm. It will be economically challenging for uptakes of these, or similar, AMU reduction scenarios on farms if the market prices become un-favorable to pig farmers.